Identifying as Christian in an alien public arena - Miner, Maureen; Stephens, Mark (Ancient Historian) (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Although Christianity is the world's largest religion, there is confusion over what it means to be Christian within contemporary society. For individuals it is difficult to find, form, or receive a Christian identity, let alone maintain a Christian identity, within a secular world. Within organizations such as the church and professions there is often a disconnection between public and private identities and the reality of being Christian in our culture. For society there is the problem of disparate portrayals of Christianity, the marginalized status of Christianity with an associated lack of influence of Christians on our society, and the ongoing shaping of Christian identity by the public arena itself. Associated questions are: should Christians try to engage in, and even shape, the public arena and if so, how? This volume examines the problem of confused and misunderstood Christian identity in a post-Christian age. It suggests ways of shaping Christian identity for the benefit of individuals and for the common good. The importance of well-formed Christian identities is illustrated by research and analysis of selected professions so that the public life of Christians can be more fulfilling and effective. This book will be valuable for all those who are interested in religious identity within a secular society. People of faith and religious organizations will benefit from a penetrating analysis of what it means to be Christian today. Similarly, those whose work involves the church, counselling, education and the performing arts will find specific applications that address concerns about faith in the workplace"--